Quality improvement of health systems in an epidemic context: a framework based on lessons from the Ebola virus disease outbreak in West Africa - Brugnara Kirchmann, Lúcia; Pervilhac, Cyril; Kohler, François; Dramé, Mohamed Lamine; Sax, Sylvia; Marx, Michael (The international journal of health planning and management, 2020)
Quality improvement (QI) in health generally focuses on the provision of health services with the aim of improving service delivery. Yet QI can be applied not only to health services but also to health systems overall. This is of growing relevance considering that due to deficiencies in health systems, the main countries affected by Ebola virus disease (EVD) outbreak in West Africa (2014-2016) were insufficiently prepared for the epidemic, and according to the WHO, epidemics are increasingly becoming a threat to global health. Our objective is to analyze QI constraints in health systems during that EVD epidemic and to propose a practical framework for QI in health systems for epidemics in developing countries. We applied a framework analysis using experiences shared at the “Second International Quality Forum” organized by the University of Heidelberg and partners in July 2015 and information gathered from a systematic literature review. Empirical results revealed multiple deficiencies in the health systems. We systemized these shortfalls as well as the QI measures taken as a response during the epidemic. On the basis of these findings, we identified six specific “priority intervention areas,” which ultimately resulted in the synthesis of a practical QI framework. We deem that this framework that integrates the priority intervention areas with the WHO building blocks is suitable to improve, monitor, and evaluate health system performance in epidemic contexts in developing countries.